Penilaian Kualitas Air Berdasarkan Sistem Saprobik di Sungai Ciapus - Majariana Krisanti; Niken T.M. Pratiwi (Jurnal Perikanan Universitas Gadjah Mada, 2007)
Changes of environment could also changes the organisms, as individual, population, or community therefore the appearance of an organism could be applied as biological indicator of those environments. Simple methods were introduced in England, Australia, Thailand, and Indonesia. The objective of this study was to evaluate water quality of Ciapus river using simple kit based on saprobic system. An Illustrated cover and inserted paper were used as kit to evaluate the river water quality. Using this kit, the appearance of specific organisms were used as key to evaluate the river water quality of Ciapus River directly. Samples were taken from two segment of Ciapus River i.e. upper and middle part. According to the method, the upper segment of Ciapus River was categorized as very good condition, while the middle part was in moderate condition.